Computer aided discovery of benzimidazole derivatives on peptide deformylase as antimicrobial agent using hex - Sivakumar, Ramaraj; Pradeepchandr, Ramachanran Vasanthakumari; Jayaveera, Korlakunta Narasimha (European Journal of Chemistry, 2011)
A series of benzimidazole containing isoxazoline-5-one compounds were computationally designed and optimized with the Hex to investigate the interactions between the target compounds and amino acid residues of the Escherichia coli peptide deformylase (PDF).Ni enzyme. These compounds docked into the active site of peptide deformylase (PDB code, 1G2A) using Hex docking tools software, which showed good affinity for the enzyme when compared with the binding energies of standard drugs such as amoxicillin (-237.61) and ciprofloxacin (-229.60). Among all the designed compounds, the compound 3 shows more binding energy values (-325.17). Further, we planned to synthesis these benzimidazole derivatives and screen for in-vitro anti-bacterial effect on different microorganisms.